Development of barley introgression lines carrying the leaf rust resistance genes Rph1 to Rph15. Issue 1 (9th March 2020) - Martin, Matthew J.; Chicaiza, Oswaldo; Caffarel, Juan C.; Sallam, Ahmad H.; Druka, Arnis; Waugh, Robbie; Ordon, Frank; Kopahnke, Doris; Keilwagen, Jens; Perovic, Dragan; Fetch, Thomas G.; Jin, Yue; et al.
Abstract: In many production areas, barley ( Hordeum vulgare L.) is attacked by the leaf rust pathogen ( Puccinia hordei Otth), a basidiomycetous fungus that reduces both its yield and quality. Many leaf rust resistance genes, known as reaction to P. hordei ( Rph ) genes, have been described in barley. To differentiate genetic variants for virulence in pathogen populations, plant pathologists use differentials (i.e., sets of host lines carrying different resistance genes). The sources of Rph1–15 were derived from cultivars, landraces, and wild barley ( H . vulgare ssp. spontaneum K. Koch) accessions with diverse geographic origins and agromorphological traits. Ideal differential sets comprise single‐gene lines backcrossed to a single adapted accession that is susceptible to all known races of a pathogen. In this study, sources of Rph1–15 and other Rph gene donors were backcrossed to the susceptible barley cultivar Bowman and then genotyped to characterize the chromosomal positions and sizes of introgressions. Overall, 95 Bowman introgression lines for leaf rust resistance were developed and characterized for their rust phenotypes and genotypes. A single line was selected to represent each of the 15 Rph genes for use as the new barley leaf rust differential set. The existence of possible new resistance genes in the studied germplasm was postulated. The new Bowman Rph1–15 differential lines will facilitate the efficient virulence phenotyping of P. hordei and serve as valuable genetic stocks for Rph gene stacking and cloning in barley.